0281 Decreased Objective Total Sleep Time in APOE Ɛ4 Positive Cognitively Normal Elderly. (27th April 2018) - Miller, M D; Sharma, R A; Rivas, J; Robbins, R; Seixas, A; Giardin, J; de Leon, M J; Varga, A W; Ayappa, I; Rapoport, D; Osorio, R S; Godinho, A
Abstract: Introduction: The ApoE4 allele is one of the most important genetic risk factors for Alzheimer's disease (AD). Sleep disturbances are known behavioral symptoms of AD and have recently been reported also as a risk factor for the disease. Additionally, we know that ApoE4 carriers have a higher chance of being amyloid positive. However, it is still unclear as to how it may moderate sleep as a risk factor for AD. Recent studies suggest that cognitively normal ApoE4 carriers have decreased sleep quality and shorter subjective total sleep time (TST) compared to non-carriers, but no studies have been performed using objective sleep measurements. Thus, we hypothesized that ApoE4 carriers will have a lower objective TST when compared to non-carriers. Methods: Objective measure of TST was collected using actigraphy for 7 consecutive days, with instructions to follow their bedtime schedule. CSF and blood were collected for analyses as per standard published protocols. Amyloid positive subjects (defined as P-Tau/AB42 ratio >0.11) were excluded in secondary analyses. Group comparisons were done between ApoE4 groups using a univariate analysis. Results: 142 cognitively normal (CDR=0, MMSE [29.3 ± 0.99]) elderly (66.46 ± 7.05 years) subjects were included. 63.4% were female and 35.2% were ApoE4 carriers. Mean TST for the entire cohort was 422.26 ± 71.86 minutes. There was a significant difference in TST for ApoE4 carriers (406.24 ± 79 mins) and non-carriers (431 ± 66.51 mins) groups; F(1, 140)= 3.91, p=0.05. Interestingly, after excluding amyloid positive participants from the analysis the results became stronger F (1, 126)=5.51, p=.02 and remained significant after controlling for age, sex, BMI, and years of education. Conclusion: Our current analysis suggests that ApoE4 positive cognitively normal are more likely to have lower objective TST prior to significant amyloid deposition. Future longitudinal studies are required to better understand the role of ApoE4 in regards to changes in sleep duration and whether their interaction increases risk of AD. These findings will help establish the role of sleep interventions as preventative measures for AD. Support (If Any): NIH/NIA/NHLBI, R01HL118624, R01HL111724, R21AG049348, R01AG035137, R01AG022374, R01AG13616, R01AG12101 and P30AG008051, K07AG052685.